Analisis Kepuasan Mahasiswa Universitas Riau terhadap Website Wayground Menggunakan Pendekatan Webuse - Boy Sandy Dwi Nugraha H.; Rahmat Hidayat; Dwi Risyfa Anggraini; Khairunisa Prina Anggitia; Tri Putri Maisyitah; Dimas Adji Isnanda; Rafi Nur Haq (Universitas Methodist Indonesia, 2026)
The development of technology in the world of education has encouraged the use of digital platforms such as Wayground to support the learning process. However, there has not been much research evaluating the level of student satisfaction with the use of the platform. This study aims to analyze the satisfaction of Riau University students with the Wayground website using the WEBUSE (Website Usability Evaluation) approach. The research method used is a quantitative survey with a questionnaire instrument based on the WEBUSE dimensions, which include aspects of usability, information quality, user interaction, and technical performance. The data collected were tested using validity and reliability analysis, with the results showing that all instrument items have a level of validity and reliability that is included in the excellent category. Based on the results of the analysis, most students are satisfied with the performance and ease of use of the Wayground website. In conclusion, this platform is considered effective and worthy of continued use in online learning activities. This study is expected to be a reference in the development of an e-learning platform that is more responsive to user needs.